Individuals and materials in the Greco-Roman cults of Isis: agents, images, and practices : proceedings of the VIth International Conference of Isis studies (Erfurt, May 6-8, 2013 - Liège, September 23-24, 2013) - Gasparini, Valentino; Veymiers, Richard (Religions in the Graeco-Roman world, 2018)
Front Matter -- Copyright page -- Preface /Vinciane Pirenne-Delforge -- Acknowledgments -- Participants -- List of Plates, Graphs and Tables -- Abbreviations -- Agents, Images, Practices* /Richard Veymiers -- -- Priests and Worshippers -- Theorising Religion for the Individual* /Jörg Rüpke -- Identités religieuses isiaques : pour la définition d’une catégorie historico-religieuse* /Giulia Sfameni Gasparro -- What is a Priest of Ēse, of Wusa, and of Isis in the Egyptian and Nubian World? /Joachim Friedrich Quack -- What is an Isiac Priest in the Greek World?* /Paraskevi Martzavou -- Les prêtres isiaques du monde romain /Laurent Bricault -- Isis Names in Graeco-Roman Egypt /Willy Clarysse -- Social Agentivity in the Eastern Mediterranean Cult of Isis* /Jaime Alvar -- Isiastai Sarapiastai: Isiac Cult Associations in the Eastern Mediterranean* /Ilias Arnaoutoglou -- Images and Objects -- L’apparence des isiaques : la réalité des stéréotypes littéraires /Ludivine Beaurin -- La figure de Pharaon dans la Mensa isiaca et ses avatars italiens. Du temple pharaonique au temple isiaque /Marie-Christine Budischovsky -- Du blanc, du noir et de la bigarrure : le jeu des couleurs dans les représentations d’isiaques /Adeline Grand-Clément -- Ministers of Isiac Cults in Roman Wall Painting* /Eric M. Moormann -- De « Scipion l’Africain » aux « prêtres isiaques » : à propos des portraits au crâne rasé avec cicatrice(s) /François Queyrel and Richard Veymiers -- Mourir en isiaque ? Réflexions sur les portraits de momie de l’Égypte romaine* /Gaëlle Tallet -- The Garments of the Devotees of Isis* /Sabine Albersmeier -- Les dévotes isiaques et les atours de leur déesse /Michel Malaise and Richard Veymiers -- Roman Children and the “Horus Lock” between Cult and Image* /Annika Backe-Dahmen -- Des empereurs aux traits isiaques ? Images et contextes* /Emmanuelle Rosso -- -- Rites and Practices -- Archéologie des Isea: sur la difficile reconnaissance des pratiques isiaques /William Van Andringa -- Material Evidence and the Isiac Cults: Art and Experience in the Sanctuary /Molly Swetnam-Burland -- Les préposés au luminaire dans les cultes isiaques /Jean-Louis Podvin -- Pèlerinages isiaques /Françoise Dunand -- Dreams and Other Divine Communications from the Isiac Gods in the Greek and Latin Epigraphical Record* /Gil H. Renberg -- Comments on the Egyptian Background of the Priests’ Procession during the Navigium Isidis* /Stefan Pfeiffer -- Jouer, chanter et danser pour Isis /Laurent Bricault and Richard Veymiers -- Les acteurs sur scène. Théâtre et théâtralisation dans les cultes isiaques* /Valentino Gasparini -- Postface* /Robert Turcan -- Plates -- Back Matter -- Bibliography.